Clozapine-carboxylic acid plasticized co-amorphous dispersions: Preparation, characterization and solution stability evaluation - Ali Ahmed Mahmoud Abdelhaleem; Ali Adel Ahmed; Maghrabi Ibrahim Abdullah (Acta Pharmaceutica)
This study addressed the possibility of forming of co-amorphous systems between clozapine (CZ) and various carboxylic acid plasticizers (CAPs). The aim was to improve the solubility and oral bioavailability of clozapine. Co-amorphous dispersions were prepared using modified solvent evaporation methodology at drug/plasticizer stoichiometric ratios of 1:1, 1:1.5 and 1:2. Solid state characterization was performed using differential scanning calorimetry, X-ray diffraction and infra red spectroscopy. Highly soluble homogeneous co-amorphous dispersions were formed between clozapine and CAPs via hydrogen bonding. The co-amorphous dispersions formed with tartaric acid (1:2) showed the highest dissolution percentage (> 95 % in 20 minutes) compared to pure crystalline CZ (56 %). Highly stable solutions were obtained from co-amorphous CZ-citric and CZ-tartaric acid at 1:1.5 molar ratio. The prepared dispersions suggest the possibility of peroral or sublingual administration of highly soluble clozapine at a reduced dose with the great chance to bypass the first pass metabolism.